2020
DOI: 10.1590/s2175-97902019000317705
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of bacterial endophytes from Myanmar medicinal plants for antimicrobial activity against human and plant pathogens

Abstract: This research aimed to investigate the antagonistic activity of the bacterial endophytes from Myanmar medicinal plants. Thirty-one bacterial isolates were isolated from Myanmar medicinal plants: Tinospora cordifolia (Wild.) Miers., Catharanthus roseus G. Don., Tectona hamiltoniana Wall. and Boscia variabilis Collett & Hemsl. (Capparaceae). Dual culture and agar well diffusion methods were used for antimicrobial assay. One endophyte from Catharanthus roseus and two bacterial isolates from Boscia variabilis Col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 18 publications
1
5
0
Order By: Relevance
“…The meristic data of brown tilapia was more or less similar to those of the NIRWANA Nile tilapia. In general, the meristic characteristics of both tilapias were in accordance with the meristic characteristics of Nile tilapia species reported from African water by previous workers [5,6], as well as with the meristic characteristics of Nile tilapia from other regions [11,[19][20][21]. Those also suggested that both tilapias might belong to the species of Nile tilapia.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…The meristic data of brown tilapia was more or less similar to those of the NIRWANA Nile tilapia. In general, the meristic characteristics of both tilapias were in accordance with the meristic characteristics of Nile tilapia species reported from African water by previous workers [5,6], as well as with the meristic characteristics of Nile tilapia from other regions [11,[19][20][21]. Those also suggested that both tilapias might belong to the species of Nile tilapia.…”
Section: Resultssupporting
confidence: 89%
“…Overall, the length-weight relationships in Nile tilapia species were reported differently, either as positive allometric (b > 3), negative allometric (b < 3), or isometric (b = 3). The Nile tilapia cultured in Bangladesh [19], Myanmar [20], India [22], Tanzania [23], and Zambia [24] were reported to have negative allometric growth of the length-weight relationship. In contrast, the Nile tilapia cultured in Thailand [25] and Kenya [26] had positive allometric ones.…”
Section: Resultsmentioning
confidence: 99%
“…The antimicrobial activity of many secondary metabolites as a mechanism to inhibit pathogens is well documented (Buatong et al 2011; Mapperson et al Gouda et al 2016; Pelo et al 2020; Myo et al 2020). Dat et al (2019) extracted 64 strains of endophytic bacteria from the mangrove plant Rhizophora stylosa and found that 14 of them inhibited pathogens including Escherichia coli , Pseudomonas aeruginosa , Bacillus subtilis , Staphylococcus aureus , and Candida albicans .…”
Section: Discussionmentioning
confidence: 99%
“…(Wani et al 2015; White et al 2016). The direct use of secondary metabolites may instead find better application in the pharmaceutical industry as microbial and antifungal agents as supported by a plethora of recent studies (Talapatra et al 2018; Arora and Kaur 2019; Mukhopadhyay et al 2020; Myo et al 2020; Pelo et al 2020; Photolo et al 2020). They may also be investigated for use in food systems as health-promoting phytochemicals.…”
Section: Practical Applicationsmentioning
confidence: 99%
“…The endophytes isolated from Catharanthus roseus and Boscia variabilis Collett & Hems not only prevent the growth of human pathogenic bacteria but also prevent plant pathogenic fungi [19]. Infection by common pathogens, such as Escherichia coli, Klebsiella pneumoniae, Streptococcus agalactiae, Salmonella typhi, Serratia marcescens, and Staphylococcus aureus, is controlled by extracts that contain large quantities of tannins, flavonoids, saponins, and phenolics produced by Bacillus siamensis and its host plant, Calotropis procera [20].…”
Section: Antimicrobial Effects Of Endophytic Bacteriamentioning
confidence: 99%